Association of Retinopathy with Chronic Kidney Disease in Diabetes Mellitus - Rouf, Rushda Sharmin Binte; Ashrafuzzaman, SM; Latif, Zafar Ahmed (BIRDEM Medical Journal, 2018)
Background: Diabetic retinopathy (DR) and nephropathy are two major complications of diabetes mellitus carrying significant morbidity and mortality. In this study DR was investigated in different stages of chronic kidney disease (CKD) to find out possible association of these two devastating complications. Methods: This cross-sectional study was conducted in 150 diabetic patients having CKD in BIRDEM. CKD was defined as estimated glomerular filtration rate (eGFR) of <60ml/min/1.73m2and/or urinary albumin excretion rate (UAER) >30 mg/day in at least two occasions in 3 months apart. Retinopathy was assessed by direct fundoscopic examination and confirmed by color fundus photography. Severe DR (SDR) included proliferative diabetic retinopathy, severe non-proliferative DR and maculopathy; whereas microaneurysm regarded as non-severe retinopathy. Results: Majority (68%) of the respondents had some form of retinopathy (38.35% SDR and 29.65% nonsevere). There was strong association between different levels of albuminuria (UAER) and DR (p<0.0001). On the contrary DR did not correspond with stages of CKD (P=0.349). Hypertension (79.5%) and dyslipidaemia (59%) were common co-morbidities. Conclusion: This study concluded that DR prevalence was more in nephropathy along with significant association with UAER. Whereas different stages of CKD was not associated with stages of DR . This finding focused the necessity of regular retinal examination irrespective of the stage of renal involvement. Birdem Med J 2018; 8(3): 210-214